198Au TRACER IN THE SEDIMENT TRANSPORT STUDY ON SEMARANG COASTAL WATERS - Supriatna (NIM 25396026/TPL), Dadang
ABSTRACT: Most nearshore aquatic system adjacent to urban centres are characterized by contaminated fine sediment deposits that are brought in from variety sources. Banjir Kanal Timur, Tambak Lorok and Tenggang are rivers that a cross of Semarang city and have a mouth at same location, that location are potential pollutant sources for Semarang coastal waters, so the knowledge of sediment transport in Semarang is very important for management and sustainable that area. One of techniques to understand transport of sediment is radioactive tracer, radioactive tracer have several major advantages: high detection sensitivity, unique and possibility of being measured in situ provide information in the shortest possible time. Specific gravity and particle size distribution analysis, indicates that there was no differences between nature sediments compare with labeled 198Au sediments. This phenomena means that labeling sediment using 198Au did not change the behavior of sediment hydrodynamics. Results of leaching analysis show the leaching constant not significant difference for salinity between 10 0/00 and 40 0/pp with the mean leaching constant was obtained 0.0165 daY-1 Contour of movement pattern of radiotracer show movement of sediment toward North, while dispersing move to left and right direction with mean velocity of 5.65 m/day. Sediment transport rate was calculated of 780.7 kg/mlday with the thickness of the mobile layer sediments 5.2 cm.